Rapid Last Glacial Maximum deglaciation in the Indian Himalaya coeval with midlatitude glaciers: New insights from 10Be‐dating of ice‐polished bedrock surfaces in the Chandra Valley, NW Himalaya. Issue 4 (22nd February 2016) - Eugster, Patricia; Scherler, Dirk; Thiede, Rasmus C.; Codilean, Alexandru T.; Strecker, Manfred R.
Abstract: Despite a large number of dated glacial landforms in the Himalaya, the ice extent during the global Last Glacial Maximum (LGM) from 19 to 23 ka is only known to first order. New cosmogenic 10 Be exposure ages from well‐preserved glacially polished surfaces, combined with published data, and an improved production rate scaling model allow reconstruction of the LGM ice extent and subsequent deglaciation in the Chandra Valley of NW India. We show that a >1000 m thick valley glacier retreated >150 km within a few thousand years after the onset of LGM deglaciation. By comparing the recession of the Chandra Valley Glacier and other Himalayan glaciers with those of Northern and Southern Hemisphere glaciers, we demonstrate that post‐LGM deglaciation was similar and nearly finished prior to the Bølling/Allerød interstadial. Our study supports the view that many Himalayan glaciers advanced during the LGM, likely in response to global variations in temperature. Key Points: Exposure ages of ice‐polished surfaces similar to moraine boulders Extensive MIS‐2 (LGM) glaciation at the southern front of the Indian Himalaya Himalayan LGM deglaciation coeval with midlatitude LGM deglaciation